Ethnic minorities on Spanish media - Sobrados León, Maritza (2022)
The most ancient ethnic minority of Spain are the Gypsies, though the intensive growth of the immigration in the last years is forcing to restate the problem of minorities. The immigration is one of the topics that more worries Spanish society and an current unsolved matter by politicians. The current foreign population already arises to four million people, whose presence provokes not few situations of rejection, to which partly contributes the diffusion of negative stereotypes by mass media.